Voltammetric Response on a Puller‐Made Nanometer‐Sized Electrode. Issue 3 (27th February 2013) - Li, Fei; Hunt, Benjamin; Sun, Peng
Abstract The method of fabrication of electrodes by using a laser‐puller is a commonly used method to produce small electrodes. Simulation shows that the taper‐shaped insulation layer of a puller‐made electrode has an obvious effect on its voltammetric response, especially when the electrode has a small RG (the ratio of the insulating sheath radius to the electrode radius). The effect of low‐pass filtering on the voltammetric response of a very small puller‐made electrode has also been studied.